FNA smears of pancreatic ductal adenocarcinoma are superior to formalin‐fixed paraffin‐embedded tissue as a source of DNA: Comparison of targeted KRAS amplification and genotyping in matched preresection and postresection samples. Issue 11 (12th October 2017) - Hartley, Christopher P.; Mahajan, Aparna M.; Selvaggi, Suzanne M.; Rehrauer, William M.
Abstract : BACKGROUND: The current study was conducted to compare DNA yield, including normalization to nuclear area, DNA amplification functionality, and detection of KRAS mutations between matched fine‐needle aspiration (FNA) specimens and pancreatic resections diagnostic of pancreatic ductal adenocarcinoma. METHODS: A retrospective sample of 30 matched single FNA smears and macrodissected formalin‐fixed, paraffin‐embedded (FFPE) curls (2 5‐μm curls) were compared by measuring the following: nuclear area (via digital image analysis), DNA yield (via NanoDrop spectrophotometry and Quantus fluorometry), and polymerase chain reaction threshold cycles for KRAS amplifications. Variants in KRAS codons 12/13 and 61 were detected by fluorescent melt curve analyses, followed by Sanger DNA sequencing. RESULTS: Despite a similar nuclear area, FNA smears yielded greater DNA per nuclear area via 2 DNA quantification methods. KRAS codon 12 mutations were detected in 23 of 30 FNA specimens (77%) compared with 17 of 30 matched FFPE specimens (57%), for a concordance rate of 74%. No KRAS codon 13 or 61 mutations were detected. CONCLUSIONS: FNA specimens are a more optimal source of DNA, and represent an important resource in the preresection and postresection molecular analysis of pancreatic ductal adenocarcinoma. Cancer Cytopathol 2017;125:838–47. © 2017 American Cancer Society. Abstract : KRAS detection is superior in fine‐needle aspiration specimens compared with single macrodissected formalin‐fixed, paraffin‐embedded blocks (2 curls measuring 5 μm each), despite similar DNA yields. In the nascent clinical application of the molecular analysis of pancreatic ductal adenocarcinoma for prognosis and therapy selection, fine‐needle aspiration material is preferable to formalin‐fixed, paraffin‐embedded resection tissue.